Financial crisis and sectoral diversification of Argentine banks, 1999-2004 (2005)
We explore the impact and evolution of loan portfolio diversification during the 2001-2002 Argentine financial crisis. Using a novel dataset that combines public information on the main activity of the largest 930 Argentine firms with their borrowing from each bank operating in the country during the 1999-2004 period, we find that banks did not modify much their loan portfolio mix as a response to the crisis, even though the econometric results point to a positive effect of sectoral diversification and lending to tradeable sectors on bank profitability and risk mitigation. Our results suggest that larger banks benefit more from diversification that smaller ones, and that the benefits of diversification are greater during the downside of the business cycle.